1996
DOI: 10.1212/wnl.47.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Isolated vertigo as a manifestation of vertebrobasilar ischemia

Abstract: Isolated vertigo can be the only manifestation of vertebrobasilar ischemia. Its frequency may be underestimated in clinical practice. Noninvasive testing is helpful both for diagnosis and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 5 publications
5
74
1
3
Order By: Relevance
“…Of 29 patients with vertebrobasilar insufficiency, 21% have episodic vertigo for at least 4 weeks as the only presenting symptom. 19,20 Moreover, patients with anterior inferior cerebellar artery infarction, anterior vestibular artery infarction, or cerebellar infarction may present with symptoms or signs similar to Meniere disease, benign paroxysmal positional vertigo, and vestibular neuritis, respectively. 5,[21][22][23] To prevent misdiagnosis of stroke in vertigo patients, vertebrobasilar insufficiency or posterior circulation infarction should be recognized as possible causes of acute-onset isolated vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Of 29 patients with vertebrobasilar insufficiency, 21% have episodic vertigo for at least 4 weeks as the only presenting symptom. 19,20 Moreover, patients with anterior inferior cerebellar artery infarction, anterior vestibular artery infarction, or cerebellar infarction may present with symptoms or signs similar to Meniere disease, benign paroxysmal positional vertigo, and vestibular neuritis, respectively. 5,[21][22][23] To prevent misdiagnosis of stroke in vertigo patients, vertebrobasilar insufficiency or posterior circulation infarction should be recognized as possible causes of acute-onset isolated vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although none of the studies included in our systematic review compared the timing of onset across disorders, two uncontrolled, retrospective case series identified in our critical review reported that dizziness was typically abrupt in onset among pa tients with a cerebrovascular cause of acute dizziness. 48,49 Prodromal dizziness None of the studies in our systematic review reported on prodromal dizziness. A critical review of other evidence on transient, isolated episodes of prodromal dizziness preceding a pres entation of acute vestibular syndrome suggested a prevalence of about 25% among patients with vestibular neuritis 50,51 and a similar prevalence among patients with vertebrobasilar stroke.…”
Section: Typementioning
confidence: 94%
“…Recurrent epi sodes were reported in two retrospective case series of patients with cerebrovascular dizziness. 48,49 In the larger series, 29% (12/42) of patients with vertebrobasilar stroke had prodromal, isolated epi sodes of dizziness for up to two years before the stroke. Note: CNS = central nervous system.…”
Section: Typementioning
confidence: 98%
See 1 more Smart Citation
“…46 Nonetheless, it could be suspected in a patient in whom only some of the vertigo attacks are accompanied by other symptoms of brainstem dysfunction such as diplopia. [47][48][49] In the absence of any simultaneous brainstem symptoms, a short history, of days rather than months, of frequent brief vertigo attacks lasting minutes rather than hours several times a day, should raise the suspicion that the attacks are posterior circulation transient ischaemic attacks (TIAs). Hearing symptoms, tinnitus and deafness, if unilateral and occurring at the same time as the vertigo attacks, suggest an aural rather than a brainstem problem.…”
Section: Diagnoses That Are Likely To Be Wrong In a Patient With Vertigomentioning
confidence: 99%